Data, informatics and technology an inspiration for improved healthcare - Hasman, Arie; Liaskos, Joseph; Househ, Mowafa, 1977-; Mantas, J. (John) (Studies in health technology and informatics ;, 2018)
Biomedical informatics is important for the entire domain of healthcare, from clinical informatics and health informatics to the wider field of public health informatics. This book presents the 80 full papers selected from the 130 submitted for review and subsequently presented at the 16th International Conference on Informatics, Management, and Technology in Healthcare (ICIMTH 2018), held in Athens, Greece, in July 2018. This important conference draws participants from the field of biomedical and health informatics from all continents to exchange a wide range of research and application outcomes in informatics from cell to population, and topics covered here include technologies such as imaging, sensors and other biomedical equipment, and management and organizational aspects such as legal and social issues and the setting of research priorities in health informatics. Data, informatics and technology continue to inspire both health professionals and informaticians to improve healthcare for the benefit of patients, and this book will be of interest to all those engaged in this endeavor.